2020
DOI: 10.3389/fphys.2020.00201
|View full text |Cite|
|
Sign up to set email alerts
|

HuangqiGuizhiWuwu Decoction Prevents Vascular Dysfunction in Diabetes via Inhibition of Endothelial Arginase 1

Abstract: Hyperglycemia induces vascular endothelial dysfunction, which contributes to the development of vascular complication of diabetes. A classic prescription of traditional medicine, HuangqiGuizhiWuwu Decoction (HGWWD) has been used for the treatment of various cardiovascular and cerebrovascular diseases, which all are related with vascular pathology. The present study investigated the effect of HGWWD treatment in streptozocin (STZ)-induced vascular dysfunction in mouse models. In vivo studies were performed using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…This mechanism has emerged as an essential factor underlying impaired endothelial functions [ 68 , 69 ]. Specifically, an increased arginase activity has been associated with endothelial dysfunction in a number of experimental models of hypertension, atherosclerosis, diabetes, and aging [ 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ].…”
Section: Pleiotropic Effects Of Argininementioning
confidence: 99%
“…This mechanism has emerged as an essential factor underlying impaired endothelial functions [ 68 , 69 ]. Specifically, an increased arginase activity has been associated with endothelial dysfunction in a number of experimental models of hypertension, atherosclerosis, diabetes, and aging [ 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ].…”
Section: Pleiotropic Effects Of Argininementioning
confidence: 99%
“…Analysis of forearm blood flow in patients with T2DM showed that arginase inhibition can ameliorate endothelium-dependent vasorelaxation, which is maintained after glucose optimization [ 9 ]. ARG1 inhibition can ameliorate streptozocin-induced vascular dysfunction through increased NO production [ 126 ]. Studies of the retinal arterioles from diabetic pigs have shown that early type 1 diabetes can increase the arginase activity, thereby impairing endothelium-dependent NOS-mediated dilation of retinal arterioles during diabetes, while arginase blockade leads to the opposite results [ 127 ].…”
Section: Arginase Contributes To Cvds Developmentmentioning
confidence: 99%
“…In HFD-induced obese mice, SC treatment remarkably inhibits HFD-induced increases in arginase activity and weights of liver and visceral fat tissue in a dose-dependent manner to reduce hepatic lipid metabolism and systemic adiposity via the suppression of hepatic arginase [ 182 ]. HuangqiGuizhiWuwu Decoction (HGWWD), commonly used for the treatment of diverse cardiovascular and cerebrovascular diseases in mice, was reported to lessen STZ-induced impairment of velocity and pulsatility of left femoral arteries; aortic pulse wave velocity and vascular relaxation enhance NO production in the aorta and plasma, as well as blunt endothelial arginase activity and aortic ARG1 expression [ 183 ]. In the type 1 DN mice model, Xiao-Shen-Formula (XSF) treatment improved STZ-induced renal hyper-filtration, glomerulosclerosis, and renal microvascular remodeling and prevented the increased of oxidative stress and inflammatory cytokines releases by ablating the increased levels of ARG2 protein and arginase activity, which was comparable to that of ABH treatment alone [ 184 ].…”
Section: Arginase Inhibitors For Dm and Its Complications Therapymentioning
confidence: 99%